Development and psychometric evaluation of "Quality of Life Scale for Asthmatic Children” (QOLSAC) - Yaghmaei, F; Aminzade, S; Noorian, M; AlaviMajd, H (Advances in Nursing & Midwifery, 2010)
Background and aim Asthma is a chronic condition affecting on quality of life (QOL) of afflicted children and their families. Nurses and other healthcare workers need a valid and reliable tool to mesure these effects. The aim of this study was to Development and psychometric evaluation of "Quality of Life Scale for Asthmatic Children” (QOLSAC). Materials and methods This research is a methodological study. A review of literature and semistructured interviews with 13 asthmatic children were carried out to develop 81 statements of “Quality of Life Scale for Asthmatic Children (QOLSAC).”The content of the scale were then validated by asking 30 professionals in pediatric medicine and nursing, asthma, tool development and QOL based on relatedness, clarity and simpleness. Statements with 75% validity or more were retained. Face validity of the scale was also identified. Construct (factor analysis) and criterion validitieswere identified by distributing the scale to 136 asthmatic children and comparing with Kindel’s QOL questionnaire respectively. Internal consistency (Cronbach’s α) and stability (test-retest) measurements were performed for the reliability of the scale. Findings Factor analysis showed 5 domains (factors) in the scale and criterion validity revealed 0.89 correlation between the 2 tools. The range of Cronbach’s α (coefficient of correlation) in the 5 domains was between 0.81 and 0.92 and test-retest measurements indicated 0.93-0.98 correlations in the domains. Conclusion The results showed that QOLSAC with 61 statements is valid and reliable, using Likert measurement scale. With respect to the importance of this scale, applying it to assess the quality of life of asthmatic children is recommended. Keywords: Scale development, Psychometric evaluation, Quality of life, Asthmatic children. *Corresponding Author: Dr. Farideh, Yaghmaei. Dept. of Community Health Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran E-mail: Farideh_y2002@yahoo.com